The role of management’s tendency and personnel’s motivation in fulfillment of brand promise - Mahmoud Samiei Nasr; Seyed Mohsen Mahmoudzadeh; Seyed Shahab Mousavi; Azadeh Boostani (Management Science Letters)
Fulfillment of the promises or brand promise plays essential role for the success of organizations. This paper presents an empirical investigation to evaluate the rate of management’s interest and personnel’s motivation in an Iranian firm named TAM Iran Khodro. The study reviews its relationship with fulfillment of corporative promises for customers. The study selects a sample of 206 employees of TAM Iran Khodro Company including managers and employees. Questionnaire is a tool for gathering information designed by the researchers. With respect to primary sample group including 40 participants, Cronbach’s Alpha coefficient was calculated as 0.905 for reliability value of this questionnaire, which validates the questionnaire. Spearman’s correlation coefficient and multiple regressions have been adopted to test different hypotheses. Research findings indicate that management’s tendency and personnel’s motivation were positively and significantly associated with fulfillment of corporative promises to customers (Brand Promise) with correlation coefficient 0.427.